Model and Methods for Estimating the Number of People Living in Extreme Poverty Because of the Direct Impacts of Natural Disasters - Rozenberg, Julie; Hallegatte, Stephane (World Bank, Washington, DC, 2016)
Natural disasters have an impact on poverty through many different channels -- economic growth, health, schooling, behaviors -- that are difficult to quantify. It is nonetheless possible to assess the short-term impacts of income losses. A counterfactual scenario is built of what people's income would be in developing countries in the absence of natural disasters. This scenario uses surveys of 1.4 million households in 89 countries. Depending on where they live and work, what they consume, and the nature of their vulnerability, the additional income that each household in the survey could earn every year on average in the absence of natural disasters is calculated. The analysis concludes that if all disasters could be prevented next year, 26 million fewer people would be in extreme poverty—that is, living on less than $1.90 a day. A systematic analysis of the uncertainty suggests that this impact could lie between 7 million if all the most optimistic assumptions are combined, and 77 million if we retain only the most pessimistic assumptions.